Poor sensitivity and consistency of microscopy in the diagnosis of low grade non-gonococcal urethritis. - Smith, R; Copas, A; Prince, M; George, B; Walker, A; Sadiq, S (2003)
OBJECTIVES: To determine the reliability of the diagnosis of non-gonococcal urethritis (NGU), and the variation between and within microscopists, from urethral smears at a large London genitourinary medicine clinic. METHODS: A senior microscopist (SM) preselected 60 Gram stained urethral smear slides, 20 negative (<5 polymorphs/hpf), 20 low grade NGU (5-20 p/hpf), and 20 high grade NGU (>20 p/hpf). Ten experienced microscopists, blinded to these initial grades, examined all slides giving each a polymorph score. After relabelling and randomly changing their order, the slides were re-examined by the same microscopists. Finally, the SM determined whether the study had resulted in loss of cells from any of the slides. The SM's initial grading and the consensus among microscopists provide two gold standards for analysis. RESULTS: Nine low grade and five high grade slides were removed from analysis because of loss of cells. By SM standard, considering microscopists' readings as simply non-NGU (<5 p/hpf) or NGU (>or=5 p/hpf), 97% from negative slides were correct (variation 93-100 across microscopists), 68% from low grade slides (45-95), and 94% from high grade slides (83-100). Consistency between repeat readings by the same microscopist was 96% for negatives, 75% for low grade and 89% for high grade slides. Results were similar by consensus standard. CONCLUSIONS: There was considerable variation between and within microscopists in the diagnosis of NGU. Sensitivity was strongly related to grade of urethritis, with an appreciable proportion of low grade urethritis falsely diagnosed as negative. With increasing attendances for sexual health screening, a false positive rate of only 3% may lead to many false diagnoses.